ANALISIS KEAMANAN ARSIP DIGITAL DALAM ADMINISTRASI RUMAH SAKIT - Hanisa Zuria Syafitri; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2026)
Digital transformation in the healthcare sector through the implementation of Electronic Medical Records (EMR) and digital archives has become a key strategy for improving the efficiency and quality of public services. However, this transition faces significant challenges related to data security, patient privacy, and human resource readiness. This article aims to analyze health information security management strategies and formulate steps to optimize digital transformation. This research uses a qualitative approach with library research through secondary data collection from the internet, including scientific journals, official reports, and government regulations. The findings indicate that despite the availability of technologies such as electronic signatures and access control, security risks often arise due to human error and incomplete standard operating procedures (SOPs). Strategies for strengthening infrastructure, ongoing digital literacy training for healthcare workers, and synchronizing national policies are key to ensuring the integrity and confidentiality of patient data.